Öjingsvallen vid sjön Öjingen - Karlsson, Hanna (2005)
By using pollen analysis and 14C-dating, the history of vegetation and land use at the old shieling place (Sw: fäbodställe) Öjingsvallen in Ängersjö parish, central Sweden, was studied. The aim of the study was to answer the following questions: